Developing Communicative English Syllabus for Midwife's Students at Bengkulu University - Damba Reja Winanda; Hilda Puspita; Ildi Kurniawan (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2022)
This research is a development research with the aim of developing an English syllabus based on a communicative approach aimed for midwife’s students at Bengkulu University. Needs analysis is used in this study to determine the English language needs of midwife’s students. The instruments used in this study were questionnaires and interviews. The research population was midwife’s students at the Bengkulu University, midwifery lecturers, English lecturers, and midwives at the Bentiring Permai Public Health Center. The first sampling technique was random sampling for 50 midwife’s students, the second technique used total sampling for 1 midwifery lecturer, 1 English lecturer and 2 midwives at the Bentiring Permai Health Center. The results of the data analysis showed that speaking skills is the skill most needed by midwife’s students. Based on the results of the data analysis, the researchers designed a syllabus based on a communicative approach that had been validated by the validator.